THE DEVELOPMENT OF THE JUDICIARY ON THE TERRITORY OF UKRAINE IN THE 20TH-21ST CENTURIES AND THE FORMATION OF A MODERN DEMOCRATIC SYSTEM, AS WELL AS A JURY TRIAL - Palamarchuk, Serhii (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the proposed scientific research is the analysis of the historical development of the judiciary and the judicial system in Ukraine, the emergence and development of the jury trial and the identification of modern problems of the jury trial in Ukraine. It was established that in the course of the historical development of the jury system in Ukraine, various changes and definitions of jurors took place. First of all, it should be noted that the jury court existed in the Russian Empire and despite the shortcomings in their activity, researchers considered it a democratic direction of development in the judicial system. After the revolution of 1917 in the Soviet Union, all courts ceased their activities. Instead, new courts were created, which included people’s assessors in the judicial teams. In the process of improving the activity of the courts, people’s assessors were equalized in rights with judges, but the mentioned issue was rather conditional, because the level of education of people’s assessors was low, and there were practically no lawyers among them. Research methods: the dialectical method of cognition, general scientific and special research methods are used in the work. In particular, structural-functional, deductive methods and the method of scientific forecasting. Results as a result of the analysis of the development of the judiciary in Ukraine, it was established that the changes that took place in the process of creating one or another model of the judiciary differed to some extent from the processes of the development of the judiciary in democratic states. In the Soviet Union, an attempt was made to create to a certain extent "people’s courts" by forming a corps of people’s assessors, which to some extent corresponded to the model of a shortened jury trial, but the activity of people’s assessors was limited to approving the decisions of professional judges. At the same time, the formation of jury courts, unlike the courts of people’s assessors, took place in Ukraine for a long time. After the collapse of the Soviet Union, people’s assessors were still provided for by law in Ukraine until 2016, but they did not play any role in the judicial process. Only after the Revolution of Dignity and the adoption of the new law "On the Judiciary and the Status of Judges" were people’s assessors removed. Discussion: however, the problem of the judiciary in the Soviet Union at the beginning of its existence did not only concern people’s assessors. Almost immediately after seizing power, the Bolsheviks organized revolutionary tribunals that carried out extrajudicial activities, and their sentences in most cases included the death penalty. At the same time, the actions of the revolutionary tribunals did not have any signs of a judicial process. During the trial, defense lawyers were not allowed into the process, appeals were prohibited, and the process itself took place over several days. Especially the issue of destroying the "class enemy" developed during Stalin’s rule. First of all, people’s assessors did not have the rights that were provided for in the legislation of that time, and they were practically extras in the judicial process. This form of citizen participation in the judicial process existed until the collapse of the Soviet Union. After gaining independence, people’s assessors still remained in the first normative documents that determined the structure of the courts. At the same time, their role was also reduced to extras. Later, the concept of juror appears in the legislation of Ukraine, but it is used together with the concept of people’s assessors. And only after the Revolution of Dignity in the new Law of Ukraine, the concept of people’s assessors disappears and the concept of a juror is formed. However, until today in Ukraine, a clear concept of a juror has not been formed, and in particular, their status and activity in the judicial process has not been defined